A Comparative Study of Academic Achievement and Motivation of Adolescents in Relation to Their Mental Health in Pathankot, Punjab - Neena Chhikara; Lubhawani Tripathi (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Today's educational landscape, students navigate constant academic demands and emotional strain, making motivation and mental health essential for their development. It is critical to understand the link between these psychological factors and students’ performance for the holistic development of a student. This study is important in Indian context, especially in Pathankot, considering the unique adolescent socio-cultural influences. It specifically examines the connections of academic motivation with mental health and health achievements among higher secondary school students, emphasizing gender differences. Employing a descriptive correlational design, the study sampled a total of 1,008 students (504 boys and 504 girls) from secondary schools in Pathankot using stratified random sampling. Academic motivation and mental health were evaluated with standardized instruments while academic achievement was obtained from school records. The relationships were analyzed using Pearson’s correlation coefficient at the 0.05 level of significance. Strong positive correlations were observed between mental health and academic motivation for both girls (r = 0.453) and boys (r = 0.473). These results suggest that students who are more motivated academically tend to have better mental health. Furthermore, girls (r = 0.24) and boys (r = 0.23) exhibited moderate positive correlations between academic motivation and achievement, indicating that higher motivation tends to result in better performance. This reinforces the importance of the connection between motivation, mental well-being, and achievement. These findings support the development of more tailored educational policies and pedagogical techniques that account for students’ gender-specific needs in secondary education to cultivate mental resilience alongside strong motivational drivers for their psychological development.
Keywords: Academic Motivation; Mental Health; Academic Achievement; Higher Secondary Students; Gender Differences; Pathankot